PENINGKATAN KEMAMPUAN MENULIS PUISI DENGAN PENDEKATAN KONTEKSTUAL PADA SISWA KELAS VIIIC SMP NEGERI 13 BENGKULU SELATAN - Misti Sulastri (Universitas Bengkulu, 2017)
The research purpose to know increasing poem written ability for VIIIC grade student SMP Negeri 13 of Bengkulu Selatan by the contextual approach. The aspect that show here is the use of aim, diction, language style and imagine. The use a class action with three cycle Wich is written by students on poem, this research use class action with two. The result of the reseach show, there is differences the student ability to write the poem, with contextual opproach at SMP Negeri 13 of Bengkulu Selatan. The aim of the reseach can be seen foom the result of proces. Learng at cycle I with the avarage score 71,33. With the enaught catagories, th inpoment at cycles II with avarage score 76,14 with enaught catagories and th inpoment at cycles III with avarage score 82,14 with good catagories.Kata Kunci: write, poem, Contextual Approach